TINGKAT KELULUSAN UJI KOMPETENSI MAHASISWA PROGRAM PROFESI DOKTER (UKMPPD) PERIODE MEI MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS ABULYATAMA - Syarifah Nora Andriaty; Ade Kiki Riezky (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Graduation level of the competency test of the professional doctor program students (UKMPPD) is a test that implemented to select the medical student in order to achieve the competent doctor. Graduation of UKMPPD on Medical Profesi Program Medicine Faculty of Abulyatama until now can be said is still very low, which many graduates who did not pass UKMPPD test. Index cumulative achievement (IPK) is one of component advances or learning achievement. The objective study of this research is to find out the relation between Index cumulative achievement (IPK) profesi with the result of UKMPPD first taker. This study is quantitative research with analytical approach by using croos sectional design. There are 105 samples in this research. In selecting the sample the researcher used total sampling technique. The researcher collected the data needed from 21th June-16th July 2017 in Medical Faculty of Abulyatama University. In analyzing the data, the researcher used Chi Square text by using some Statistical Product and Service Solution (SPSS). The result of study shown that there is no significant relation between IPK Profesi in 2007, 2008, 2010, and 2011 (p-value: 0,352) with the result UKMPPD test. From the results of the research, it is expected that the teaching staff/lecturers can give more attention especially to the students of the doctor's professional education program and to improve the quality of the graduates, the faculty is expected to always provide and improve the educational support facilities and infrastructures.Keywords: IPK Profesi, UKMPPD, Place of KKS